STRATEGI KEBERHASILAN VAKSINASI DI SEKOLAH MENENGAH PERTAMA NEGERI 2 JULI KABUPATEN BIREUEN - akbar, muhammad; khalisni, khalisni (Program Studi Ilmu Politik, Universitas Syiah Kuala, Banda Aceh, 2023)
Vaccination at State Junior High School 2 Juli failed in the first stage. The failure was caused by the community's fear of the adverse effects of giving vaccinations. Regarding this phenomenon, the government evaluated and improved the situation by providing education and picking up the students who wanted to be vaccinated directly. The result of this effort conducted by the government was known to improve the success of vaccination, giving up to 80 %. The result revealed that the policy of providing vaccination to the students of State Junior High School 2 of Juli was considered appropriate and suitable to be implemented since it had fulfilled three essential elements as mentioned by Hesel; (1) rational, in which the aim of vaccination was to maintain the health of the students of State Junior High School 2 of Juli; (2) realistic, it means the vaccination policy was needed in a pandemic situation which is getting worse and can threaten everyone's health and life; (3) accurate, it means that the policy is based on considerations that the transmission has occurred in the school environment and there were recommendations from the authorities that vaccination was safe form minors. The strategy used in implementing the vaccination policy at State Junior High School 2 of July was divided into three critical stages, namely the formulation in the form of coordination of task division by relevant agencies, implementation within the scope of vaccination implementation, and evaluation regarding improving conditions resulting from deficiencies that occurred in the previous implementation stage. Keywords: Covid-19, Strategy, Vaccination